Treatment of Oral Mucosa Diseases with Medicinal Plants - qizi Mirzayeva, Zubaydaxon Odiljon; Zakirjanova, Diyora Zakirjanovna (American Journal of Biodiversity, 2025)
This article provides information about the traditional treatment of oral mucosal diseases and medicinal plants that can cure this disease.